The feasibility of the posterior tibial nerve-flexor hallucis brevis pathway applied in neuromuscular monitoring: a multicentric, controlled, and prospective clinical trial - Chen, Weiqiang; Chen, Zhijian; Cheng, Fang; Wang, Zhuodan; Li, Juan; Li, Shangrong; Xie, Hanbin (PeerJ, 2024)
This study aimed to investigate the clinical viability of utilizing the flexor hallucis brevis as an alternative site for neuromuscular monitoring compared to the conventional adductor pollicis. Patients were recruited from three medical centers. Cis-atracurium was administered, and two monitors were employed independently to assess neuromuscular blockade of the adductor pollicis and the ipsilateral flexor hallucis brevis, following a train of four (TOF) pattern until TOF ratios exceeded 0.9 or until the conclusion of surgery. Statistical analysis revealed significant differences in onset time, duration of no-twitch response, spontaneous recovery time, and total monitoring time between the two sites, with mean differences of −53.54 s, −2.49, 3.22, and 5.89 min, respectively (P < 0.001).The posterior tibial nerve-flexor hallucis brevis pathway presents a promising alternative for neuromuscular monitoring during anesthesia maintenance. Further investigation is warranted to explore its utility in anesthesia induction and recovery. Trial registration: The trial was registered at www.chictr.org.cn (20/11/2018, ChiCTR1800019651).
Keywords: Neuromuscular blockade; Neuromuscular monitoring; Flexor hallucis brevis; Adductor pollicis; Cis-atracurium